Evaluating the Impact of Leadership Development - 2nd Edition - Patterson, Tracy; Stawiski, Sarah; Hannum, Kelly; Champion, Heather; Downs, Holly (Center for Creative Leadership, 2017)
Driving impact while managing resources are what most organizations strive to balance in their leadership-development efforts. Evaluation provides a practical framework for gathering and making sense of information to better manage resources while assessing the success of leadership-development efforts. This second edition of Evaluating the Impact of Leadership Development is a practical guide for human-resource professionals, consultants, managers, employees, and volunteers who have leadership-development or evaluation responsibilities in their organizations and want to enhance their practice and demonstrate the value of their work.